Systemic Therapy Use and Outcomes After Relapse from Preoperative Radiation and Extrapleural Pneumonectomy for Malignant Pleural Mesothelioma. (26th November 2018) - Soldera, Sara V.; Kavanagh, John; Pintilie, Melania; Leighl, Natasha B.; de Perrot, Marc; Cho, John; Hope, Andrew; Feld, Ronald; Bradbury, Penelope A.
Abstract: Background: Multimodality therapy with preoperative radiation (RT) followed by extrapleural pneumonectomy (EP) for patients with operable malignant pleural mesothelioma (MPM) has demonstrated encouraging results. At relapse, there are few data on the tolerance and efficacy of systemic therapies after prior multimodality therapy. Materials and Methods: We conducted a retrospective analysis of patients with relapsed MPM after RT and EPP ± adjuvant chemotherapy to determine overall survival (OS; date of relapse to death) and the proportion of patients that received systemic therapy and associated response rate (RR). OS was estimated using Kaplan–Meier method and potential prognostic variables were examined. Results: Fifty‐three patients were included (2008–2016). Median OS was 4.8 months (median follow‐up 4.4 months, range 0.03–34.8). Eastern Cooperative Oncology Group (ECOG) performance status (PS) ≥2, disease‐free interval (DFI) <1 year, and hemoglobin ≤110 g/L at recurrence were associated with worse prognosis. Thirty‐six percent of patients received any systemic therapy, whereas it was omitted in 62% because of poor PS. RR was 15% (0 complete responses, 15% partial responses) in 13 individuals with response‐evaluable disease. Therapy was discontinued because of toxicity (6/15) or disease progression (5/15), and median number of cycles was four. Conclusion: Patients with relapsed MPM following RT and EPP, especially those with ECOG PS ≥2, DFI <1 year, and hemoglobin ≤110 g/L at recurrence, have poor prognosis and low RR to first‐line systemic therapy. Earlier detection and novel diagnostic markers of relapse as well as potential neoadjuvant or adjuvant systemic therapy should be investigated in future studies. Implications for Practice: The results of this study have reinforced the importance of careful selection of appropriate candidates for this combined‐modality approach and favor prompt detection of recurrence with early and regular postoperative imaging and biopsy of suspected relapsed disease along with rapid initiation of systemic therapy even in patients with very low burden of disease. Furthermore, with the emergence of new systemic agents targeting different histological subtypes of malignant pleural mesothelioma, histological sampling of recurrence could inform therapeutic decisions in the future. Abstract : This article reports outcomes of patients after relapse from preoperative radiation followed by extrapleural pneumonectomy and chemotherapy. Abstract : 摘要 背景。 对于可手术的恶性胸膜间皮瘤 (MPM) 患者，先后采用术前放疗 (RT) 和胸膜外肺切除术 (EPP) 的多学科综合治疗已经显示出可喜的结果。在复发时，关于既往多学科综合治疗之后的系统治疗的耐受性和有效性的数据较少。 材料和方法。 我们针对在 RT 和 EPP ± 辅助化疗之后复发 MPM 的患者执行了一项回顾性分析，以确定接受系统治疗的患者的总生存期(OS；复发日期至死亡)和比例以及相关的缓解率 (RR)。使用Kaplan–Meier分析方法估算 OS，并调查潜在的预后变量。 结果。 本研究包含 53 名患者(2008 年–2016 年)。中位 OS 为 4.8 个月(中位随访时间为 4.4 个月，范围介于 0.03–34.8 之间)。东部肿瘤协作组 (ECOG) 体力状态 (PS) ≥2、无病间期 (DFI) <1 年以及复发时的血红蛋白 ≤110 g/L 均与较差的预后相关。36% 的患者曾接受任何系统治疗，但是，62% 的患者因 PS 不佳而没有进行此类治疗。在 13 名可评估疾病缓解的患者中，RR 为 15%(0 例完全缓解，15% 部分缓解)。治疗因出现毒性 (6/15) 或疾病进展 (5/15) 而停止， 中位周期数为 4。 结论。 在 RT 和 EPP 之后复发 MPM 的患者，特别是 ECOG PS ≥2、DFI <1 年且复发时的血红蛋白 ≤110 g/L 的患者，在一线系统治疗时具有较差的预后和较低的 RR。在未来的研究中应对复发的早期检测和新型诊断标记以及潜在的新辅助或辅助系统治疗进行探讨。 实践意义: 本研究结果强调了为此类联合治疗方法谨慎选择候选人的重要性，支持通过针对疑似复发疾病的早期和定期术后影像学检查和活组织检查及时检测复发并迅速开展系统治疗，即使在疾病负担很低的患者中也应如此。此外，随着针对恶性胸膜间皮瘤的不同组织学亚型的全新系统药剂的出现，复发的组织学取样可以为将来的治疗决策提供信息。